Principles of supply chain management a balanced approach - Wisner, Joel D. (South-Western, 2011)
This unique edition presents extensive content not covered in other books. An expansive approach guides readers through the management stages of each supply chain activity while addressing real-world concerns related to the global supply chain. Readers follow the natural flow through the supply chain with one of the most balanced supply chain management approaches available. Well-organized chapters and numerous new cases demonstrate practical applications of supply chain management in today's workplace, while intriguing profiles build on topics and ensure that readers cover today's most important contemporary supply issues in depth.